A 13th century shipwreck with cog features, investigated off Skeppstad, western Sweden - von Arbin, Staffan (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
This paper accounts for the preliminary investigations of a well-preserved shipwreck with several distinct cog features, discovered in Jorefjorden on the Swedish west coast and dated to the early 1260s. Investigations revealed a vessel with straight posts, clinker-built sides, and through-beams supported by large standing knees. Since the bottom section of the hull is missing it is uncertain whether it too was clinker-built, or if it was constructed with flush-laid planking in the so-called bottom based tradition, characteristic for vessels of the cog type. Furthermore, the paper discusses the shipwreck in relation to both contemporary European maritime transport geography and the local context of the site.